PENGGUNAAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI PADA PESERTA DIDIK KELAS V UPTD SD INPRES OEBA 2 KUPANG - Suban Sina, Silvester; Robot, Marselus; Musa, Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low poetry writing skills of fifth-grade students at UPTD SD Inpres Oeba 2 Kupang. The initial condition showed that students' ability to write poetry was still low due to learning that tended to use conventional lecture and question-and-answer methods, which caused students to face difficulties in expressing their ideas creatively. This study aimed to improve poetry writing skills through the implementation of the CTL model. This study employed Classroom Action Research (CAR) conducted in two cycles, comprising planning, implementing, observing, and reflecting stages. The subjects of this research were 21 fifth-grade students of UPTD SD Inpres Oeba 2 Kupang. Data collection techniques included tests, observations, and documentation, while data analysis was conducted using descriptive quantitative and qualitative methods. The results showed that the implementation of the CTL model significantly improved students' poetry writing skills. In the pre-cycle stage, the class average score was 34 with a classical completeness rate of 0%. After the intervention in Cycle I, the average score increased to 66.19 with a classical completeness rate of 14.28%. A more optimal improvement occurred in Cycle II, where the average score reached 81.90 and the classical completeness rate achieved 100%. Improvements were also observed in the poetry assessment aspects, including thematic relevance, diction, figurative language, imagery, as well as poetry structure and typography. Thus, it can be concluded that the CTL model is effective in improving the poetry writing skills of fifth-grade students at UPTD SD Inpres Oeba 2 Kupang.